2017
DOI: 10.3390/ijms18122612
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Oxidative Stress and Inflamm-Aging in Human and Equine Asthma

Abstract: Aging is associated with a dysregulation of the immune system, leading to a general pro-inflammatory state of the organism, a process that has been named inflamm-aging. Oxidative stress has an important role in aging and in the regulation of immune responses, probably playing a role in the development of age-related diseases. The respiratory system function physiologically declines with the advancement of age. In elderly asthmatic patients, this may contribute to disease expression. In this review, we will foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 217 publications
(293 reference statements)
1
34
0
3
Order By: Relevance
“…Evidences have revealed the role of oxidative stress in the pathogenesis of asthma (Bullone and Lavoie, 2017;Kleniewska and Pawliczak, 2017). The ROS in asthma could come from resident cells or immune cells.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Evidences have revealed the role of oxidative stress in the pathogenesis of asthma (Bullone and Lavoie, 2017;Kleniewska and Pawliczak, 2017). The ROS in asthma could come from resident cells or immune cells.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…There is no current correlation between inflamm‐aging and the development of chronic inflammatory airway diseases. However, based on the human phenotype, we believe it is biologically appropriate to use RAO as an equine model for late‐onset asthma, as recently reviewed …”
Section: Late‐onset Asthmamentioning
confidence: 99%
“…Numerous studies have shown that oxidative stress plays an important role in the pathogenesis of asthma (6)(7)(8). When airway inflammation occurs, inflammatory mediators such as histamine and leukotriene are released.…”
Section: Introductionmentioning
confidence: 99%